PRECEPT: GROUP ASSIGNMENT - Armstrong, Elizabeth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Background By 1994, the results of trials in the US and France showed that when AZT was given to HIV positive pregnant women prenatally, during labor, and to their newborn infants, the incidence of HIV infection was reduced by two thirds. Based on the results of this trial, this regimen was recommended by the US Public Health Service to become standard practice of care for HIV positive women in the U.S. The drug, as you might imagine, is expensive. The expense is so great that it is prohibitive for most non-developed countries to provide for their citizens. A year later, the WHO convened and issued a report stating that given the cost of the drug, more research into a less expensive regimen was needed. They supported the use of "placebo-controlled trials" to find a cheaper regimen (less AZT). In such a trial, one group receives the experimental regimen and the other receives a placebo.